The Effect of Material, Social and Activities Compensations toward Work Performance Using Organizational Commitment as The Mediator - Widyaningsih, Meilana (Faculty of Islamic Economics and Business, Institut Agama Islam Negeri (IAIN) Surakarta, 2016)
This study aims to determine the effect of material compensation, social compensation, and activities compensation on work performance through organizational commitment as the mediator. This study retrieved data through questionnaires (surveys). The population in this study were all employees of PT. Tiga Serangkai Pustaka Mandiri Surakarta, with taking 150 respondents for sampling purpose. Sampling technique in this study was a simple random sampling. The data were processed using Structural Equation Modeling (SEM) with the help of Analysis of Moment Structure (AMOS) version 20.0. The results of the data analysis found that 1) There is a significantly positive influence of social compensation variables on organizational commitment; 2) There is a positive significant effect of activity compensation on organizational commitment; 3) There is a significantly positive effect of activity compensation on job performance; 4) Organizational commitment does not mediate material compensation, social compensation, and activities compensation on job performance. Keywords: material compensation, social compensation, activities compensation, work performance, and organizational commitment, Tiga Serangkai Pustaka Mandiri